Effects of knee frontal plane position on pedal forces during cycling: A preliminary study - Fernando Diefenthaeler; Felipe Pivetta Carpes; Rodrigo Rico Bini (Universidade Federal de Santa Catarina, 2009)
The purpose of this study was to compare the force applied to the pedal when cycling with the knees almost touching the bicycle frame (adduction position) compared to the position usually adopted by cyclists (reference position) and a position of the knees away from the bicycle frame (abduction position). Six cyclists were evaluated. Maximal oxygen uptake (VO2MAX) was defined, and then the three different knee positions on the frontal plane were assessed. Three minutes of cycling in the reference position, adduction position and abduction position were conducted, using oxygen uptake (VO2) at which the cyclists had achieved the second ventilatory threshold. An instrumented two-dimensional pedal was used to measure the forces applied to the right pedal. The average VO2 and power output did not differ between the adduction (50.4±6.9 ml.kg-1.min-1 and 263±29 W), abduction (50.8±5.9 ml.kg-1.min-1 and 250±46 W) and reference position (50.4±5.9 ml.kg-1.min-1 and 246±47 W). Pedaling cadence increased significantly during adduction (94±8 rpm) and abduction (95±5 rpm) compared to the reference position (89±8 rpm). The force results indicated no differences in the effective force or effectiveness index between the reference, adduction and abduction positions. Resultant force increased during adduction (284.5±44.5 N) compared to the reference position (246.9±39.2 N). The results indicate that the cyclists were able to generate higher resultant force during cycling with the knees close to the bicycle frame, but were unable to effectively transmit this force to the movement.